Comparison of Islamic Education According to the Perspectives of K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari: Historical Roots and Curricular Implications - Irfan Ahmad Zain; Mohamad Erihadiana; Rifdaa Aulia; ‘Ainul Mardhiyyah; Sheila Mafaiza; Dicky Alfian Nur Rachman (FKIP - Universitas Riau, 2026)
Islamic education in Indonesia was significantly shaped by early twentieth-century reform movements led by K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari. This study aims to analyze comparatively the relationship between intellectual genealogy (sanad) and the curricular structure formulated by K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari. It addresses the analytical gap concerning the limited examination of how historical-sanad foundations shaped institutional curriculum design. Using a qualitative historical-comparative approach and content analysis, this research examines primary sources such as Adabul ‘Alim wal Muta‘allim and early Muhammadiyah statutes, supported by relevant secondary literature. The findings show that Ahmad Dahlan developed an integrative and modern school-based curriculum combining religious and general sciences for social transformation, while Hasyim Asy'ari reinforced a pesantren-based curriculum centered on classical scholarship, sanad continuity, and moral formation. The study demonstrates that these curricular differences are causally rooted in their distinct epistemological orientations and interpretations of religious authority. It concludes that the research successfully establishes a systematic link between intellectual genealogy and curricular construction, contributing a historical-genealogical framework for understanding the complementary diversity of Islamic education models in Indonesia.